Chemogenetic engagement of different GPCR signaling pathways segregates the orexigenic activity from the control of whole-body glucose metabolism by AGRP neurons - Valerie Espinal Abreu; Rachel Barnes; Vishnupriya Borra; Jennifer Schurdak; Diego Perez-Tilve (Molecular Metabolism)
Objective: The control of energy balance involves neural circuits in the central nervous system, including AGRP neurons in the arcuate nucleus of the hypothalamus (ARC). AGRP neurons are crucial for energy balance and their increased activity during fasting is critical to promote feeding behavior. The activity of these neurons is influenced by multiple signals including those acting on G-protein coupled receptors (GPCR) activating different intracellular signaling pathways. We sought to determine whether discrete G-protein mediated signaling in AGRP neurons, promotes differential regulation of feeding and whole-body glucose homeostasis. Methods: To test the contribution of Gαq/11 or Gαs signaling, we developed congenital mouse lines expressing the different DREADD receptors (i.e., hM3q and rM3s), in AGRP neurons. Then we elicited chemogenetic activation of AGRP neurons in these mice during the postprandial state to determine the impact on feeding and glucose homeostasis. Results: Activation of AGRP neurons via hM3q and rM3s promoted hyperphagia. In contrast, only hM3q activation of AGRP neurons of the hypothalamic arcuate nucleus during the postprandial state enhanced whole-body glucose disposal by reducing sympathetic nervous system activity to the pancreas and liver, promoting glucose-stimulated insulin secretion, glycogen deposition and improving glucose tolerance. Conclusions: These data indicate that AGRP neurons regulate food intake and glucose homeostasis through distinct GPCR-dependent signaling pathways and suggest that the transient increase in AGRP neuron activity may contribute to the beneficial effects of fasting on glycemic control.